(untitled) (Al-Mashadir: Journal of Quranic Sciences and Tafsir, 2026)
This article examines the concept of the human senses in the Qur’an as elaborated in the book I’jāz Ṭibbī by Sa’id Ṣāliḥ al-Fayyūmī and its correlation with modern medicine. (al-Fayyūmī, n.d.)This study aims to analyze the extent to which al-Fayyūmī’s explanation of hearing, vision, skin as the center of pain, the neck as a vital structure, and the mechanism of sleep corresponds with contemporary physiological, neurological and anatomical principles. (Blume et al., 2019; Medic et al., 2014). The method used is qualitative research based on literature studies by using I’jāz Ṭibbī as the primary source and reputable medical journal articles as secondary sources. The results of the study show that the description of the human senses in al-Fayyūmī’s work is in line with modern scientific findings, especially in the aspects of the function of the auditory system during sleep, the relationship between emotional states and vision, the role of nociceptors on the skin, the vitality of the neck structure, and the protective and restorative functions of sleep. (Basbaum et al., 2009; McEwen, 2007; Moore et al., 2011). This research contributes to the strengthening of the study of i’jāz ṭibbī as a relevant interdisciplinary approach in contemporary Qur’an studies without making it a book of science.